Primary Care Patient Social Networks and Tobacco Use: An Observational Study - Jaya Aysola; Jeffrey Rewley; Chang Xu; Marilyn Schapira; Rebecca A. Hubbard (SAGE Publishing, 2022)
Importance: Tobacco use remains the leading cause of preventable deaths and is susceptible to social influence. Yet, we know little about the characteristics of primary care social networks and how they influence tobacco use. Objective: To determine what primary care patient social network characteristics are associated with individual smoking behavior. Design: Cross-sectional. Setting: Two primary care practices in West Philadelphia, Pennsylvania (PA), USA. Participants: A random sample of 53 primary care patients and 155 of their nominated social ties. Main Outcome and Measures: We examined the association between social network characteristics (degree, communicated weighted social ties, and presence of social reinforcement) and tobacco use history (never smoker, successful quitter, or current smoker). Other covariates included age, race/ethnicity, sex, education, income, and employment status, self-efficacy, depression status, provider-patient relationship. Results: Of those enrolled in our study (n = 208), 101 identified as never smokers, 59 as successfully quitters, and 48 as current smokers. Social reinforcements from connected alter pairs that never-smoked (OR = 1.20, 95% CI: 1.08, 1.34) was significantly associated with a participant being a never smoker. Participants with stronger ties with successful quitters were significantly more likely to identify as successfully quitting (OR = 1.37, 95% CI: 1.11, 1.69) and conversely had a negative association with stronger ties to unsuccessful quitters (OR = 0.59, 95% CI: 0.44, 0.80) or current smokers who had not tried to quit in the last year (OR = 0.82, 95% CI: 0.68, 0.98). Social reinforcement from connected pairs of alters that were unsuccessful quitters was significantly associated with the participant being a current smoker (OR = 1.26, 95% CI: 1.10, 1.45). Conclusions: Our study suggests that smoking behaviors do not occur in isolation, nor because of 1 or 2 prominent social network members. Rather, our findings suggest that both strong ties and social reinforcement from clusters of similarly-behaving persons influence smoking behavior. Primary care practices have an opportunity to leverage these insights on patient networks to improve cancer prevention.